Sir William Keith of Delny: courtier, ambassador and agent of noble power - Kerr-Peterson, Miles (The Innes review, 2016)
Sir William Keith of Delny was the illegitimate son of a Buchan laird, who rose through the young King James VI's chamber to become Master of the Wardrobe. He also served as ambassador for James to various countries, most remarkably in the failed mission to save Mary Queen of Scots from English execution. This article explores the nature of James's reliance on lesser men as courtiers, in his trust in individuals to deliver his sentiments and how his favour could be won, lost and regained. It also explores the same dynamics in the relationship between William and his kinsman superior, George Keith, fourth earl Marischal. William is shown to be one of Jacobean Scotland's great intermediaries, between earl and king, king and courtiers, king and foreign governments.